Parallel Cycles for the Emergy Evaluation of Information in Manufacturing, Culture, and Life - Abel, Thomas (Ecological Questions, 2024)
For environmental accounting, the incorporation of human cultural information is challenging. In 1987, Howard T. Odum published an emergy analysis of highways in Texas. The highways were conceived as typical environmental-industrial products; however, his analysis incorporated the unusual feature of evaluation of the information required. Information for highway use was in the production of highway maps, which was his principal object of information study. However, in addition, he also evaluated the information for the control of highway production in specification documents. His study addressed the creation of both information forms, and the evaluation of that information with emergy. In this paper, that analysis is re-examined considering a theoretical and methodological advancement in the study of material production with information control. That advancement is the modelling of two distinct forms of information that are required for any manufactured or information product. That modelling makes use of the ‘information cycle’, a systems design that assures the maintenance and perpetuation of information against Second Law depreciation of information carriers. The two information forms are labeled here the object information and the expression information. The object information is the template for the final product (the ‘design specs’ for a widget, the script of a play, or the DNA of an organism). The expression information in cultural production is the operating procedures, standards, and conventions for setting, venue, or factory that enable the object, while in life, the expression information is the programmed behavior of the organisms and organs of reproduction. Based on the ‘information cycle’, this paper uses Odum’s highways study to demonstrate a ‘parallel cycles’ model for the perpetuation of the two forms of information.